Association between physical activity level and cardiovascular disease: An empirical analysis based on CHARLS data in 2018 - Haiwei Li; Liang Luo; Jing Zhang; Yanhao Zhao; Peipei Cheng; Dan Liu; Liwei Guo (PLoS ONE, 2025)
Objective Cardiovascular disease (CVD) was a global public health challenge. This study aimed to investigate the association between physical activity level (PAL) and CVD among middle-aged and older adults in China, to provide evidence to inform strategies for CVD prevention and management. Methods The diagnosis of CVD was based on self-reported physician-diagnosed heart disease or stroke, while PAL were classified using calculations derived from a structured questionnaire. Both datasets were obtained from the 2018 China Health and Retirement Longitudinal Study (CHARLS) survey. A multivariate logistic regression model was used for the primary correlation analysis. Additionally, restricted cubic spline (RCS) regression was employed to examine the potential nonlinear association between PAL and CVD. Results The final analysis included 9,015 participants, 1,069 of whom were diagnosed with CVD, yielding a prevalence of 11.86%. After adjusting for all covariates, the multivariate-adjusted odds ratios (ORs) for the moderate PAL group (600−3000 MET-minutes/week) and the high PAL group (>3000 MET-minutes/week) were 0.79 (95% CI: 0.64–0.97) and 0.72 (95% CI: 0.60–0.87), respectively, compared to the low PAL group (<600 MET-minutes/week). Furthermore, restricted cubic spline analysis revealed a significant linear relationship between PAL and CVD (nonlinear P > 0.05), indicating that the OR for CVD decreased with higher levels of PAL. Conclusions This study revealed a negative correlation between PAL and the prevalence of CVD. Furthermore, our findings suggested that middle-aged and older adults should maintain moderate to high levels of physical activity, as this was associated with a lower risk of CVD.